Peat fire mapping using GIS based multi-criteria decision making: study area of Kuala Langat, Selangor / Ainon Nisa Othman … [et al.] - Othman, Ainon Nisa; Ismail, Hazrul Nizam; Khalid, Nafisah; Abdul Halim, Maisarah; Mohamad Saraf, Noorain (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2019)
Peat fire is a geological disaster that causes damages to nature, human activities and environment. It is a geological phenomenon that involves a wide range of forest fire, vegetation burnt surface and smouldering fire underground. Besides that, there are other contributing factors affecting the peat fire and can lead to the forest fire disaster. In this study, GIS and MCDM Technique were used as a tool to generate the prediction of peat fire potential area map at Kuala Langat, Selangor. All the input is then being analyse in ArcGIS software. Many criteria may contribute to the peat forest fire incident such as land use, temperature, pH value, and soil type criteria. The main benefit for analysing the potential area is the possibility to prevent and predict peat fire occurrences in future other than as a precaution step to face the problems.